2 - La structure bancaire dans le processus de financement de l’économie camerounaise: 10.4314/ad.v26i2.22141 - Eze, Donatien Eze (Africa Development, 2001)
The purpose of this paper is to study the role of the banking structure in thevfinancing of the Cameroonian economy. It questions whether the banking structure determines the type of financing and if the type of financing requires a specific structure of the banking industry? The paper not only highlights the strong influence of the banking structure inherited from the colonial era on the nature of financing, but also draws attention to the reverse relationship resulting from the reaction of economic agents in the face of credit rationing. For a more efficient banking system, the Cameroonian monetary policy makers could create favourable conditions which limit the number of banks but increase their size, and also favour the integration of tontines, which are the main component of the informal financial sector. These could serve as relays between banks and low-income economic agents, who remain excluded from the formal financing networks. Such a change should be accompanied by a change in the very nature of Cameroonian banks. Priority would therefore be given to local banks and regional groups, for which the collection of internal resources is a fundamental condition for growth.